Squamous cell carcinoma of the tongue in an elderly female: a case report - Ardisa Pramudita; Inges Prawita Sari; Gina Niscita Amisesani; Hanggoro Tri Rinonce; Fajar Waskito; Dyah Ayu Mira Oktarina (Published by Universitas Gadjah Mada, 2026)
Oral squamous cell carcinoma (OSCC) accounts for approximately 90% of oral malignancies and most frequently involves the mobile tongue, where it is associated with substantial functional impairment and mortality. Although OSCC is classically associated with tobacco and alcohol exposure, it may also occur in patients without a history of active smoking or alcohol use. We report a case of HPV DNA-negative, well-differentiated invasive squamous cell carcinoma of the ventrolateral mobile tongue in a 72-year-old woman. The patient presented with a three-month history of a progressively enlarging tongue lesion accompanied by pain, difficulty eating, and unintentional weight loss. She denied active smoking, alcohol consumption, and betel quid use but reported passive exposure to tobacco smoke. Clinical examination revealed an exophytic erythroleukoplakic lesion involving the ventrolateral tongue, along with multiple missing teeth and untreated dental caries. Histopathological examination of a punch biopsy demonstrated invasive nests of malignant squamous epithelial cells with keratin pearl formation, prominent intercellular bridges, and invasion into the underlying connective tissue and muscle, consistent with well-differentiated HPV-negative squamous cell carcinoma.. Following multidisciplinary evaluation, the patient underwent induction TPF chemotherapy (docetaxel, cisplatin, and fluorouracil), followed by hemiglossectomy with modified radical neck dissection and adjuvant radiotherapy. This case highlights that persistent lesions of the mobile tongue in elderly patients warrant careful evaluation, even in the absence of active smoking and alcohol use history. Early biopsy, thorough histopathological assessment, and multidisciplinary management are essential for timely diagnosis and appropriate treatment planning.